2023
DOI: 10.1021/acsaem.2c03891
|View full text |Cite
|
Sign up to set email alerts
|

BiVO4-Decorated Graphite Felt as Highly Efficient Negative Electrode for All-Vanadium Redox Flow Batteries

Abstract: Recently, discovering high-performance electrocatalytic materials for vanadium redox flow batteries (VRFBs) has been one of the most crucial tasks. This paper details the successful fabrication of a low-cost platelike bismuth vanadate (BiVO 4 ) material through a simple one-step hydrothermal route, employed as an electrocatalyst to adorn graphite felt (GF) for use as the negative electrode in VRFBs. The experimental results show that BiVO 4 -3h exhibits the optimal electrocatalytic activity and reversibility f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…9a) as a negative electrode for VRFBs. 111 The electrocatalytic reaction mechanism of BiVO 4 -GF on V 2+ /V 3+ redox coupling was elucidated. The experimental results showed that BiVO 4 -3 h exhibited the best electrocatalytic activity and reversibility of vanadium redox pairs in all samples.…”
Section: Cost-effective Improvised Methodsmentioning
confidence: 99%
“…9a) as a negative electrode for VRFBs. 111 The electrocatalytic reaction mechanism of BiVO 4 -GF on V 2+ /V 3+ redox coupling was elucidated. The experimental results showed that BiVO 4 -3 h exhibited the best electrocatalytic activity and reversibility of vanadium redox pairs in all samples.…”
Section: Cost-effective Improvised Methodsmentioning
confidence: 99%
“…In additive processes, new materials are applied to the fibre surface. These materials can be heteroatoms (metals or nonmetals), [38,[54][55][56] graphene, [57,58] carbon dots, [59] carbon nanosphere, [60,61] carbon nanotubes (CNT), [50,62,63] reduced graphene oxide, [63,64] or other carbon. [51,65] The surface area and defect concentration play a significant role in the final performance of the electrode.…”
Section: Additive Methodsmentioning
confidence: 99%
“…[6,143,144] However, the reaction kinetics of these materials are often poor and therefore require further treatment to enhance the electrode surface to better facilitate the vanadium reactions. Common treatment methods include thermal,, [145][146][147] chemical, [46,[148][149][150][151] electrochemical oxidation, [32,152] etching, [153] the deposition of metals [154] and metal oxides, [56,155] and the use of nanomaterials such as CNTs. [57,59,156] These methods aim to modify the chemical composition, surface structure, electrochemically active surface area, conductivity, wettability, or a combination of these characteristics.…”
Section: Edge Site Defects and Heteroatom Doping Of Graphite For Vana...mentioning
confidence: 99%